2022
DOI: 10.1089/cyber.2021.0252
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Playing Video Games on Stress, Anxiety, Depression, Loneliness, and Gaming Disorder During the Early Stages of the COVID-19 Pandemic: PRISMA Systematic Review

Abstract: During the initial phases of the COVID-19 pandemic, playing video games has been much more than just a pastime. Studies suggested that video games for many individuals have helped to cope with such difficult life experience. However, other research indicates that gaming may have had harmful effects. Within this context, this systematic review aimed to describe the literature on the effects of video games during the early stages of the COVID-19 crisis on stress, anxiety, depression, loneliness, and gaming disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 122 publications
0
48
1
1
Order By: Relevance
“…Fernandes et al (2020) reported that gaming addiction among adolescents was associated with both loneliness and poor sleep quality during the COVID-19 pandemic. Similarly, other studies have reported gaming addiction to be associated with increased levels of loneliness and insomnia during the pandemic (Pallavicini et al, 2022;Zaman et al, 2022). The gaming industry saw three times more user engagement and 30% higher traffic in online mobile gaming at the start of the pandemic (Amin et al, 2022).…”
Section: Internet Gaming During the Covid-19 Pandemicmentioning
confidence: 67%
“…Fernandes et al (2020) reported that gaming addiction among adolescents was associated with both loneliness and poor sleep quality during the COVID-19 pandemic. Similarly, other studies have reported gaming addiction to be associated with increased levels of loneliness and insomnia during the pandemic (Pallavicini et al, 2022;Zaman et al, 2022). The gaming industry saw three times more user engagement and 30% higher traffic in online mobile gaming at the start of the pandemic (Amin et al, 2022).…”
Section: Internet Gaming During the Covid-19 Pandemicmentioning
confidence: 67%
“…A learning community could be a safe environment where they might experiment with teaching with other faculty members or students. For instance, according to some authors [ 62 , 63 ], it is possible for students to engage in “pedagogy of discomfort” in learning communities. The pedagogy of discomfort is a process of self-examination that requires students to critically engage with their ideological traditions and ways of thinking about issues such as racism, oppression, and social injustice.…”
Section: Results On the Effectiveness Of Distance Education In Pandem...mentioning
confidence: 99%
“…However, in the case of at-risk individuals (especially male youth), playing video games had detrimental effects such as stress, anxiety, depression, loneliness, and GD symptoms. 15 …”
Section: Gaming Type and Genre As Important Mediators Of Desirable An...mentioning
confidence: 99%